O novo mapa da população rural brasileira - Alexandre Gori Maia (Confins, 2015)
This paper analyzes the main demographic changes in the rural areas of Brazil between 1991 and 2010. Results highlight that, though with a slight slowdown in the 2000s, the rural exodus persists in all regions, either in those very dynamic as well as in the poor ones. The level of educational attainment is an important determinant of the rural exodus, which reinforces the propensity of the youngsters, particularly women, to leave the rural residence in search of better opportunities of employment, income and social stability. The rural family is now characterized by a couple with only one child in school age and with a greater dependence on older relatives with income from pensions. Finally, the paper discusses the implications of these changes to the sustainability of the agricultural activity in the medium and long term, especially for small and vulnerable family production units.